The Impact of Behaviour and Emotions of Children with Cerebral Palsy on their Skills of Daily Activities as well as their Parent`s Quality of Life - Aušra Jasaitytė; Daiva Petruševičienė; Eglė Lendraitienė (Lithuanian Sports University, 2019)
Reseach background. Cerebral palsy is a disorder of movement or position resulting from the immature encephalon defect or damage. Level of independence, behavioural and emotional skills of children with cerebral palsy are some of the main parameters of social development. Psychological factor is very important, too. Independent movement disorders and lack of professional help cause a lot of psychological problems in adolescence - depression, nervous excitement, at the time when they begin to understand that they are different from their peers. On the other hand, diffculties which they experience are not short-term, which can be overcome by mobilization of forces and the available internal resources, therefore child's adequacy also highly depends on the parents' quality of life. The goal of research was to evaluate behavioural and emotional impact on children's with cerebral palsy skills of daily activities as well as their parents' quality of life. Methods. The survey was conducted from May 2014 till April 2015 in Kaunas medical institutions which provided rehabilitation services for children. 30 children with cerebral palsy and their parents participated in the study. Average age of children who participated in the study did not differ signifcantly depending on gender and was 11.6 ± 2.1 years. Results. After the assessment of behavioural and emotional functions of children with cerebral palsy it became clear that they were the most successful in not talking back and swearing near adults. After the assessment of daily activity skills for children with cerebral palsy, it was obtained that the task which was performed the best by the children was communication, and the worst - cooking, bathing and taking the shower, as well as housework. Assessment of parents' quality of life showed that the best evaluated by parents was their ability to perform what, in their opinion, was necessary in everyday activities, the worst - favourable physical environment for their health. Assessing the impact of behaviour and emotions on children's with cerebral palsy skills of daily activities, statistically signifcant association was obtained (p < 0.05) between the scales of emotional and behavioural functions and parents' quality of life among children with cerebral palsy. The study did not show statistically signifcant difference between children's gender, age, and form of the disease. Conclusions. Children's with cerebral palsy behaviour and emotions had signifcant inﬂuence on their daily living skills (p < 0.005). Children's with cerebral palsy behaviour and emotions were mostly connected to their ability to use the toilet; the least connection was related to preparation / dressing skills. Children's with cerebral palsy behaviour and emotions had a signifcant inﬂuence on their parent's quality of life (p < 0.005). Children's with cerebral palsy behaviour and emotions affected their parent's environment and health the most, and the least they affected parent's negative emotions. Keywords: cerebral palsy, behaviour, emotions, quality of life.